In Silico Analysis of Phytoestrogens' Neuroprotective Effect on N-methyl-D-aspartate (NMDA) Receptors - Muslikh, Faisal Akhmal; Pratama, Rizki Rahmadi; Ma'arif, Burhan; Gondokesumo, Marisca Evalina (Journal of Islamic Medicine, 2023)
cause of death and disability globally. One of the causes is associated with cell signaling disorders, neuronal apoptosis, inflammation, and the deposition of aggregate proteins. The N-methyl-D-aspartate (NMDA) receptor is a glutamate receptor that, when activated, causes synaptic dysfunction and leads to neuronal death. Phytoestrogen compounds are able to replace the role of estrogen in maintaining body homeostasis, including in the CNS.  Objectif: This study aims to determine the role of phytoestrogen compounds in inhibiting NMDA activation (1PBQ), which causes neurodegenerative diseases. Methods: The method used is molecular docking with the AutoDockTools 1.5.6 program. The prediction of pharmacokinetic and pharmacodynamic properties used SwissADME, while the toxicity used pkCSM and ProTox II. Results:  The results of docking using the 1PBQ protein showed that the compounds α-amyrin, β-amyrin and eudesmin had the best binding potential compared to 17β-estradiol which was the positive control. Pharmacokinetic and pharmacodynamic tests showed that the three compounds had good permeability and strong lipophilicity, so they could penetrate cell membranes, and were not toxic, except for eudesmin, which was included in class IV in the toxicity test using ProTox II. Conclusion :   α-amyrin and β-amyrin compounds have the potential to treat neurodegenerative diseases against NMDA receptors (1PBQ).